Lexical Anaphors and Pronouns in Liangmai - Everaert, Martin; Subbārāo, Kārumūri V.; Mataina, Wichamdinbo (Lingua Posnaniensis, 2013)
This paper discusses some aspects of the behavior of anaphors and pronouns in Liangmai, belonging to the Tibeto-Burman language family. W e show that Liangmai offers a unique combination of “reflexivization strategies”. Like other languages it exhibits the strategy of reflexivizing the predicate by reduplication of an anaphoric element, but it simultaneously marks the predicate with a self-element. Two more properties of anaphoric properties of Liangmai are interesting from a cross-linguistic perspective. It shows cases of “swapping” - reordering of differently case-marked elements within the complex anaphor - and long-distance binding - allowing an anaphoric element to refer to an element that is not a co-argument.